Sevoflurane and the Neonatal Brain: A Statistical Meta-Analysis of Potential Impacts - O. Ababneh, Muawieh; A. Shehab, Refaat; J. Alkayed, Omair; Khatib, Wael; Al-Nabulsi, Mozon Muhib Samih; Al-Buti, Firas G.; T. Alsaad, Abdul Rahman (Journal of Neonatal Surgery, 2025)
We performed a systematic meta-analysis to determine the neurodevelopmental effects of sevoflurane anesthesia in neonates. Although sevoflurane has favorable pharmacokinetics, making it a mainstay in neonatal anesthesia, preclinical studies suggest sevoflurane may have potential neurotoxicity during critical brain development. We searched PubMed, Embase, and Cochrane Library from inception to April 2015 and, using a prespecified search strategy designed to identify studies of any clinical outcome, identified 376 records (354 PubMed/Embase, 22 other sources). After removing 36 duplicates, 2 articles were excluded if authors provided only data from sevoflurane–specific groups, and then we screened 340 titles/abstracts, of which 25 were assessed in full text; 22 were excluded due to lack of a control arm, no data on animals, and so on. Of the three studies included, one was a randomized controlled trial, and two were observational cohorts with 550 subjects (242 exposed and 308 controls). Standardized IQ scores (FSIQ), cerebral palsy, and motor deficits were extracted. Mean differences (MD; continuous outcomes) or odds ratios (OR; binary outcomes) with 95% confidence intervals (CI) were applied in random‐effects models, and p < 0.05 denoted significance. There was no significant difference in cognitive outcomes: pooled MD in FSIQ was –0.24 points (95% CI: –3.60 to +3.12, p = 0.889; I² = 0%). On the other hand, there was markedly increased odds of cerebral palsy (adjusted OR ≈ 5.09; p < 0.05; I² = 70%) and other motor impairments in infants extremely preterm exposed to sevoflurane. However, we were limited in the amount of behavioral problem data, but they suggested that difficulty may be in the modest direction for parent‐reported behaviors. Sevoflurane exposure during early neonatal life does not compromise global cognitive development by early childhood but may increase the risk of motor neurodevelopmental problems in vulnerable preterm populations. These findings support the continued use of sevoflurane in the neonate, provided careful monitoring is in place and support ongoing follow‐up and investigation into protective strategies for the high-risk infant.